Biomimetic fabrication of highly ordered laminae–trestle–laminae structured copper aero-sponge. Issue 16 (9th April 2020) - Huang, Jiankun; Zeng, Jingbin; Wang, Hongbin; Etim, Ubong J.; Liang, Baoqiang; Meteku, Edem B.; Li, Honglin; Wang, Yiyan; Qiu, Zhiwei; Rood, Mark J.; Yan, Zifeng
Abstract : Light-weight metallic aero-sponges are highly desirable for electronics, energy storage, catalysis and environmental remediation. Abstract : Light-weight metallic aero-sponges are highly desirable for electronics, energy storage, catalysis and environmental remediation. Although several fabrication methods have been developed, the mechanical strength and the structural fatigue resistance of the metallic aero-sponges remain unsatisfactory. Loofah sponge is known for its mechanical strength and grease absorption due to its highly ordered hierarchical laminae–trestle–laminae (L–T–L) microstructure. Inspired by this structure–function relationship, we engineered a highly ordered L–T–L structured copper aero-sponge by unidirectional freeze-casting of copper nanowires (CuNWs) and polyvinyl alcohols (PVA). By this approach, water-to-ice crystallization shaped the building blocks into vertically distributed microchannels and horizontally arranged hollow pores. The copper aero-sponge exhibits anisotropic mechanical elasticity with a maximum tolerable compressive stress of 57 kPa, sustainable resilience at a strain of 75% and structure-induced hydrophobicity with a water contact angle more than 130°. The elasticity and hydrophobicity of the copper aero-sponge are also superior to those of the mimicked loofah sponge and copper aero-sponge with disordered pore structure made by the conventional freeze-casting. This work can be extended to manufacture novel bioinspired aero-sponges/aero-gels with hierarchical ordered microstructures.